Singapore: National report for the Global Access to Justice Project - EUGENE, Tan K. B. (Institutional Knowledge at Singapore Management University, 2021)
Global Access to Justice Project is gathering the very latest information on the impact of the world’s major justice systems, analyzing legal, economic, social, cultural and psychological barriers that prevent or inhibit many, and not only the poor, from entering and using the legal system. The country report for Singapore follows the common framework provided by the Global Access to Justice Project Questionnaire.